OCCURENCE OF ADVERSE EVENTS DUE TO CONTINUOUS GLUCOSE MONITORING - Jadviscokova, Tereza; Fajkusova, Zuzana; Pallayova, Maria; Luza, Jiri; Kuzmina, Galina (Biomedical papers, 2007)
Aims: Continuous glucose monitoring (CGM) using transcutaneous sensors is becoming a sophisticated method to control and regulate glucose metabolism. The transcutaneous sensor of the CGM system (CGMS™ Medtronic Minimed, Northridge, CA, USA) is chosen to measure glucose concentration in interstitial fluid up to three days after insertion even though its function remains stable for a longer period. The question arises, which factors really limit the period of sensor insertion without unnecessary risk. The aim of this study was to assess any adverse events occurring in the course of 9 days after the sensor insertion.Methods: In a group of 22 healthy volunteers aged 21.8 extpm1.30 y (mean extpm SE) a total of 26 sensors was inserted subcutaneously in gluteal or lumbar region for 9 days. Before insertion the site was sprayed with an antiseptic (Cutasept F, Bode Chemie, Hamburg, Germany). Local adverse reactions and disturbances in general condition were examined.Results: In the course of 184 sensor-days, there were only minor local adverse events: hypersensitivity, itching, pain, redness, burning, subcutaneous hemorrhage. Additionally, sleep disturbances, attention deficits, problems related to the CGMS monitor, to adhesive tape and/or sensor were found. None of these resulted in sensor withdrawal. In 12 volunteers (55 %) no complications were observed. The sensor function measured according to electrical signals (ISIG) failed (always on day 1-2) in 4 cases (16 %).Conclusions: The present FDA approved 3-day insertion period for Medtronic transcutaneous sensor does not seem to limit its use and appears to be worth a careful revision.
Keywords: Continuous glucose monitoring/Sensors/Adverse events